PENGARUH EARNINGS MANAGEMENT TERHADAP KONSERVATISMA AKUNTANSI - FIVI ANGGRAINI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2008)
The objective of the research is to find out empirical evidence of the influence of earnings management on conservatism accounting. The population of the study was listed companies in the manufacturing sector at the Jakarta Stock Exchange, and the sample was determined based on the following criteria manufacturing business publishing financial statement of per 31 December. There were 58 companies meeting the criteria. Data analysis was carried out in terms of financial report during 2001-2006. The hyphoteses of research were tested using logistic regression. The research prove that if related by earnings management, company manager tend to use the accountancy which conservative not will limit the action of opportunistic management. The results show that earnings management influence conservatism accountancy is not consistent used company in Indonesia because still the existence of some of more opting company to use the conservative accountancy or use the accountancy is not conservative.